Role of Chloroquine phosphate on Acute phase reactant in patients with knee osteoarthritis - Turki, Kismat M. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: The acute phase response is a major pathophysiologic phenomena that accompanies inflammation whether acute or chronic. The complements 3 (C3), complement4 (C4) and C-reactive protein (CRP) are positive acute phase proteins (+ve APPs) their production is increased by hepatocyte in osteoarthritis (OA). Chloroquine (CQ) which is a diprotic weak base traditionally used to treat malaria.Todate, the phosphate salt of CQ is used to decrease +ve APPs. Objective: To evaluate the role of chloroquine phosphate on acute phase proteins C3, C4 and Creactive protein in patients with knee OA. Subjects and methods :A total of seventy four patients (45 female and 29male) were selected randomly from the outpatients clinic in Baghdad teaching Hospital, Medical City, Baghdad suffering from knee OA were treated with oral dosage form of CQP for one month, twice daily. The levels of C3, C4 and C-reactive protein in serum of all patients were measured before and after treatment using ELISA technique.The serum level of C3, C4 and C-RP were calculated as mean ± standard error of mean (SEM); paired t-test was used; S= significant, P value < 0.05 Results :The levels of C3, C4 and C-RP were significantly reduced (P< 0.05) in serum of all patients after treatment with CQP for one month. Conclusion :CQP is a disease modifying anti rheumatic drug (DMARD) used for patients suffering from KOA in order to reduce their C3, C4 and C-RP value and improves the disease status.